Late-occurring chromosome aberrations and global DNA methylation in hematopoietic stem/progenitor cells of CBA/CaJ mice exposed to silicon (28Si) ions - Kanokporn Noy Rithidech (2018)
© 2015 Elsevier B.V. Although myeloid leukemia (ML) is one of the major health concerns from exposure to space radiation, the risk prediction for developing ML is unsatisfactory. To increase the reliability of predicting ML risk, a much improved understanding of space radiation-induced changes in the target cells, i.e. hematopoietic stem/progenitor cells (HSPCs), is important. We focused on the in vivo induction of late-occurring damage in HSPCs of mice exposed to 28 Si ions since such damage is associated with radiation-induced genomic instability (a key event of carcinogenesis). We gave adult male CBA/CaJ mice, known to be sensitive to radiation-induced ML, a whole-body exposure (2 fractionated exposures, 15 days apart, that totaled each selected dose, delivered at the dose-rate of 1cGy/min) to various doses of 300MeV/n 28 Si ions, i.e. 0 (sham controls), 0.1, 0.25, or 0.5Gy. At 6 months post-irradiation, we collected bone marrow cells from each mouse (five mice per treatment-group) for obtaining the myeloid-lineage of HSPC-derived clones for analyses. We measured the frequencies of late-occurring chromosome aberrations (CAs), using the genome-wide multicolor fluorescence in situ hybridization method. The measurement of CAs was coupled with the characterization of the global DNA methylation patterns, i.e. 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC). A dose-dependent increase in the frequencies of CAs was detected (Analysis of Variance or ANOVA, p < 0.01), indicating the induction of genomic instability after exposure of mice to 300MeV/n 28 Si ions. Slight increases in the levels of 5mC were observed in all treatment groups, as compared to the sham-control level. In contrast, there was a significant reduction in levels of 5hmC (ANOVA, p < 0.01). Since these endpoints were evaluated in the same mouse, our data suggested for the first time a link between a reduction in 5hmC and genomic instability in HSPC-derived myeloid colonies of CBA/CaJ mice exposed to 300MeV/n 28 Si ions.